A randomized, double blind trial of prophylactic fibrinogen to reduce bleeding in cardiac surgery - Sadeghi,Mostafa (2014)
BACKGROUND AND OBJECTIVES: Postoperative bleeding has a great clinical importance and can contribute to increased mortality and morbidity in patients undergoing coronary artery bypass graft surgery. In this prospective, randomized, double-blind study, we evaluated the effect of prophylactic administration of fibrinogen concentrate on post-coronary artery bypass graft surgery bleeding. METHODS: A total of 60 patients undergoing coronary artery bypass surgery were randomly divided into two groups. Patients in the fibrinogen group received 1 g of fibrinogen concentrate 30 min prior to the operation, while patients in the control group received placebo. Post-operative bleeding volumes, prothrombin time, partial thromboplastin time, INR, hemoglobin and transfused blood products in both groups were recorded. A strict red blood cell transfusion protocol was used in all patients. RESULTS: There were no significant differences between intra-operative packed red blood cells infusion in the studied groups (1.0 ± 1.4 in fibrinogen group, and 1.3 ± 1.1 in control group). Less postoperative bleeding was observed in the fibrinogen group (477 ± 143 versus 703 ± 179, p = 0.0001). Fifteen patients in the fibrinogen group and 21 in the control group required post-op packed red blood cells infusion (p = 0.094). No thrombotic event was observed through 72 h after surgery. CONCLUSION: Prophylactic fibrinogen reduces post-operative bleeding in patients undergoing coronary artery bypass graft.